(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2005)
This paper considers the analysis of the non-linear mechanical response of a laminate constituted of 12 layers of glass fiber/ epoxy resin tested in uniaxial tension until the failure at constant imposed displacement rates. The non linearity observed of mechanical behaviour in shear under uniaxial tension for the specimens oriented at 45° tested "test at 45°" has "plastic" nature. The law exponentiel proposed for the tangent shear modulus has plastic nature and refers to the plastic flow of the matrix. This model precises the evolution of the tangent shear modulus depending on the mechanical state characterized by the shear strain.